Finite-element modelling for the assessment of tunnel-induced damage to a masonry building - Yiu, W; Burd, H; Martin, C (Thomas Telford (ICE Publishing), 2017)
The likely severity and extent of cracking damage in existing masonry buildings caused by shallow tunnelling in urban areas is typically assessed in practice using a phased sequence of calculations of increasing complexity. If initial assessments (e.g. with the building modelled as an elastic beam) suggest that damage could be significant, or for buildings with high heritage value, it may be appropriate to conduct more detailed assessments using three-dimensional (3D) numerical analysis. This paper demonstrates the application of 3D finite-element modelling in this context. Models are developed to quantify the effect of shallow tunnelling on an example masonry building founded on strip footings, considering both single- and twin-tunnel scenarios in a typical London soil profile. The analyses use appropriate constitutive models for the soil and the masonry, and allow for the possibility of slippage or gapping at the soil–foundation interface. The results presented here focus on the interaction between the soil and the building (by way of its foundations) and on the influence of explicitly modelled window and door openings. It is shown that useful damage predictions can be obtained from 3D analysis of a single facade and foundation, without the need to model a complete building. The study also highlights some of the limitations of current elastic beam assessment methods.